Perceived power resources in situations of collective action - Insa Theesfeld (Water Alternatives, 2011)
This paper discusses various concepts of power. Its goal is to shed light on a better method for implementing the power concept. The case of Bulgaria's water user associations' failure shows the abuse of power by local actors who fear they will lose their influence and the private benefits that they have enjoyed under the former system. The paper provides an empirical study of power resources verified by actors' perceptions rather than having resource endowments quantified. It also illustrates the contrast between empirically revealed perceived power resources in a local context and their theoretical examination in the Distributional Theory of Institutional Change. Studies that set power resources in relation to one another are scarce. Therefore, in this study an innovative, interactive method is used that leads to a ranking of perceived power resources, which is robust against the impact of belonging to different territorial, social, and agricultural producer groups: 1) unrestricted access to information, 2) personal relationships, 3) trustworthiness, 4) cash resources for bribing, 5) menace, and 6) physical power and violence. The implication of this gradation of power resources on collective action solutions addresses complementary measures to disseminate information and compensation measures for those who fear losing their benefits and may therefore oppose the new institutions.
Keywords: 330; collective action; power concepts; nonparametric testing; irrigation; Bulgaria